Das Restglied asymptotischer Entwicklung der Dichtefunktionen - Survila, P. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Сурвила. Остаточный член асимптотического разложения для плотностейP. Survila. Tankio funkcijos asimptotinio išdėstymo liekamasis narys